2006
DOI: 10.1523/jneurosci.3372-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Regulation of Slick and Slack K+Channels by Neuromodulators

Abstract: . We now report that activity of both Slo2 channels is controlled by neuromodulators through G␣ q -protein coupled receptors (GqPCRs) (the M 1 muscarinic receptor and the mGluR1 metabotropic glutamate receptor). Experiments coexpressing channels and receptors in Xenopus oocytes show that Slo2.1 and Slo2.2 channels are modulated in opposite ways: Slo2.1 is strongly inhibited, whereas Slo2.2 currents are strongly activated through GqPCR stimulation. Differential regulation involves protein kinase C (PKC); applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 57 publications
(61 reference statements)
7
107
0
Order By: Relevance
“…Bithionol, a bis-phenol compound known for its antiparastic actions, potently activates Slack currents (Yang et al 2007). Activation of PKC increases the amplitude of Slack-B currents and decreases the amplitude of Slick currents (Santi et al 2006). Furthermore, a recent study shows that the Slick and Slack subunits coassemble to form heteromeric channels that differ from the homomers in their unitary conductance (Chen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Bithionol, a bis-phenol compound known for its antiparastic actions, potently activates Slack currents (Yang et al 2007). Activation of PKC increases the amplitude of Slack-B currents and decreases the amplitude of Slick currents (Santi et al 2006). Furthermore, a recent study shows that the Slick and Slack subunits coassemble to form heteromeric channels that differ from the homomers in their unitary conductance (Chen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both channel subunits contain large C termini consisting of tandem RCK domains (regulators of K ϩ conductance) (Jiang et al, 2002;Ye et al, 2006) with many consensus PKA and protein kinase C (PKC) phosphorylation sites (Joiner et al, 1998;Bhattacharjee et al, 2003). Although sensitive to PKC regulation (Santi et al, 2006), recombinant Slack channels are unresponsive to PKA modulation (Nuwer et al, 2009). Most of the PKA consensus in Slack are located outside the RCK domains, suggesting that PKA modulation of Slack K Na channels should not affect gating but could involve protein-protein interaction and consequently trafficking of channels.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have localized and identified K Na channels in the principal neurons of the MNTB and have compared their properties with those of Slack and Slick expressed in oocytes and mammalian cell lines (Joiner et al, 1998;Bhattacharjee et al, 2003;Yuan et al, 2003;Santi et al, 2006;Yang et al, 2006). Current-clamp recordings from MNTB neurons and numerical simulations indicate that the activation of these K Na channels allows temporal accuracy of firing to be increased at high frequencies of stimulation.…”
Section: Introductionmentioning
confidence: 99%